Activated carbon and method for producing the same

By mixing the low-grade carbon black with the activation catalyst in a polar solvent and heating it at a medium temperature, the problem of high-temperature and hazardous chemicals in the prior art is solved, and the effect of producing high-performance activated carbon is achieved at low cost and efficiently.

CN115916698BActive Publication Date: 2025-02-18NATIONAL UNIVERSITY OF SINGAPORE +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202180039007.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2021-03-31
Publication Date
2025-02-18
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

When converting low-grade carbon black into high-value activated carbon, the prior art requires high temperature and hazardous chemicals, resulting in high energy consumption and safety risks, and high production costs.

Method used

By combining chemical and physical activation methods, low-grade carbon black is mixed with activation catalysts such as ammonium persulfate in a polar solvent and heated at a temperature of 350°C to 500°C to form activated carbon with high surface area and adsorption capacity.

Benefits of technology

The production of high-performance activated carbon at low cost and low energy consumption is achieved, reducing raw materials and processing costs, while improving yield and product environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115916698B_ABST
    Figure CN115916698B_ABST
Patent Text Reader

Abstract

The present invention generally relates to a method for forming activated carbon. The method for forming activated carbon includes mixing carbon black with an activating catalyst and heating the carbon black to form activated carbon. The present invention also relates to the use of the activated carbon disclosed herein. In a preferred embodiment, the activating catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate, or a combination thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to methods for forming activated carbon. The present invention also relates to uses of the activated carbon disclosed herein. Background Art

[0002] In recent decades, the incineration of carbon waste has caused serious air and soil pollution to the environment. This operation has caused problems such as potential toxicity to the environment and loss of valuable materials. This carbon waste contains a large amount of valuable heavy metals and carbon black that can be used in various industrial applications. From an economic and environmental point of view, it is necessary to recover low-grade carbon from carbon waste and further convert it into value-added materials. Instead of incineration, converting carbon black waste into value-added products is an emerging field in the global community. Carbon black (CB) is a carbon-based material with nanoparticle size. Their significant properties include large surface area, excellent electron transport properties and chemical properties. Due to these significant properties, these carbon nanomaterials have been developed for various applications such as water treatment, pigments, optoelectronics, solar energy collection, and conductive fillers. However, the structural properties of CB, mainly its particle size and porosity, depend to a large extent on the raw materials (petroleum, coal or natural gas) and the manufacturing method. Carbon black leached from carbon black waste is considered to be a low-grade material due to its poor physical and chemical properties. As a result, the consistency of the resulting properties of mass-produced CB impregnated materials is low.

[0003] Many physical and chemical treatments have been developed to convert low-grade carbon into high-value end products. Existing physical activation requires extremely high temperatures (>800°C) in the presence of steam, air, CO2, N2, and inert gases. Chemical activation involves the use of highly hazardous chemicals such as nitric acid, phosphoric acid, sulfuric acid, and potassium hydroxide to cause activation. The high energy consumption of physical activation and the use of hazardous chemicals during chemical activation are the main disadvantages of these technologies.

[0004] The activated carbon market is a fast-growing market where demand outstrips supply. In addition, there are more and more restrictive regulations set on production due to the above-mentioned issues. The global market potential is expected to be around $26 billion in 2025, of which the Asian market is expected to be around $5 billion.

[0005] It would be desirable to overcome or ameliorate at least one of the above problems, or at least provide a useful alternative. Summary of the invention

[0006] The present invention relates to a method for producing activated carbon. In particular, the present invention relates to converting low-grade carbon black, such as carbon black extracted from refinery waste, into activated carbon by combining chemical and physical activation means. This activation strategy provides activated carbon with high surface area and adsorption capacity and will advantageously reduce processing costs and raw material costs for activated carbon production. In contrast, the current practice of making activated carbon is from charcoal, which increases the cost of the activated carbon because charcoal is relatively more expensive.

[0007] The present invention relates to a method for forming activated carbon, comprising:

[0008] a) mixing carbon black with an activated catalyst in a polar solvent to form a mixture; and

[0009] b) heating the mixture at about 350° C. to about 500° C. to form activated carbon;

[0010] wherein the weight ratio of carbon black to activated catalyst is from about 1:0.1 to about 1:0.5; and

[0011] The activating catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate or a combination thereof.

[0012] Compared to the prior art which uses steam activation to produce activated carbon at temperatures above 800°C, the present invention uses low cost catalysts and moderate temperatures (<500°C) to convert low grade carbon into activated carbon. The present invention also does not require steam or pressurized systems to work. Further advantageously, the process has lower energy requirements and higher activated carbon yields than existing activation methods. It can also be used for other carbon wastes.

[0013] In some embodiments, the mixture is heated at about 400° C. for at least 3 h.

[0014] In some embodiments, the solvent is selected from water, ethanol, ethylene glycol, or a combination thereof.

[0015] In some embodiments, the solvent is a mixture of water and ethanol in a weight ratio of 85:15, a mixture of water and ethylene glycol in a weight ratio of 85:15, or a mixture of ethanol and ethylene glycol in a weight ratio of 85:15.

[0016] Advantageously, the solvent enables the carbon black and the activated catalyst to be sufficiently mixed (or completely mixed) so that the activated catalyst can be adsorbed on at least the surface of the carbon black.

[0017] In some embodiments, the weight ratio of carbon black to solvent is from about 1:5 to about 1:100.

[0018] In some embodiments, the mixture is mixed for at least 1 h.

[0019] In some embodiments, the method further comprises adding a co-catalyst to the mixture in step (a).

[0020] In some embodiments, the co-catalyst is mixed with the mixture for at least 3 hours.

[0021] In some embodiments, the promoter is ammonia or ammonium hydroxide.

[0022] In some embodiments, the weight ratio of activated catalyst to co-catalyst is about 1:0.1.

[0023] In some embodiments, the pH of the mixture is maintained at about 7 to about 9.

[0024] In some embodiments, the mixture is heated at a rate of about 1 °C / min to about 5 °C / min.

[0025] In some embodiments, the method further comprises the step of drying the mixture after step (a).

[0026] The present invention also relates to a method for forming silane-functionalized activated carbon, comprising:

[0027] a) mixing carbon black with a silane agent and an activating catalyst in a polar solvent to form a mixture; and

[0028] b) heating the mixture at about 350° C. to about 500° C. to form a silane-functionalized activated carbon;

[0029] wherein the weight ratio of carbon black to activating catalyst is from about 1:0.1 to about 1:0.5; and wherein the activating catalyst is selected from acetic acid and / or ammonia.

[0030] Advantageously, the silane agent acts as a bridging moiety in forming mesoporous activated carbon. To this end, the silane agent allows the formation of carbon-to-carbon connections between carbon particles, thereby forming pores between the carbon particles.

[0031] In some embodiments, the mixture is stirred at room temperature for at least 3 h.

[0032] In some embodiments, the mixture is heated at about 350° C. for at least 6 h.

[0033] In some embodiments, the weight ratio of carbon black to silane agent is from about 1:0.18 to about 1:0.25.

[0034] In some embodiments, the weight ratio of silane agent to catalyst is from about 1:0.5 to about 1:1.7.

[0035] In some embodiments, the silane agent is selected from bistriethoxysilane (1,2-bis(triethoxysilyl)ethane)), 1,2-bis(trichlorosilyl)ethane, 1,2-bis(trimethoxysilyl)ethane, or a combination thereof.

[0036] The present invention also relates to activated carbon formed by the methods disclosed herein.

[0037] In some embodiments, the activated carbon has a particle size of about 40 nm to about 80 nm.

[0038] In some embodiments, the activated carbon has a BET surface area greater than 600 m 2 / g.

[0039] In some embodiments, the activated carbon has a pore size of at least 1.5 nm.

[0040] In some embodiments, the activated carbon has a dye adsorption of at least 170 mg / g.

[0041] The present invention also relates to silane-functionalized activated carbon formed by the methods disclosed herein.

[0042] In some embodiments, the particle size of the silane-functionalized activated carbon is from about 140 nm to about 500 nm.

[0043] In some embodiments, the silane-functionalized activated carbon includes at least 4 carbon particles.

[0044] In some embodiments, the silane-functionalized activated carbon has a silica shell having a thickness of about 10 nm on at least the surface of the activated carbon.

[0045] In some embodiments, the BET surface area of ​​the silane-functionalized activated carbon is greater than 600 m 2 / g.

[0046] In some embodiments, the pore size of the silane-functionalized activated carbon is at least 9 nm. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Embodiments of the invention will now be described by way of non-limiting examples with reference to the accompanying drawings, in which:

[0048] Figure 1 SEM images of (a) carbon X, (b) AC-AP, and (c) AC-Si are shown;

[0049] Figure 2 TEM images of (a) carbon X, (b) AC-AP, and (c) AC-Si are shown;

[0050] Figure 3FT-IR spectra of (a) carbon X, (b) AC-AP, and (c) AC-Si are shown;

[0051] Figure 4 Raman spectra of (a) carbon X, (b) AC-AP, and (c) AC-Si are shown;

[0052] Figure 5 Shown are the XRD of (a) carbon X, (b) AC-AP, and (c) AC-Si;

[0053] Figure 6 TGA curves of (a) carbon X, (b) AC-AP, and (c) AC-Si are shown;

[0054] Figure 7 N2 adsorption isotherms of (a) carbon X, (b) AC-AP, and (c) AC-Si are shown;

[0055] Figure 8 Shown are the pore size distribution curves of (a) Carbon X, (b) AC-AP, and (c) AC-Si;

[0056] Fig. 9 shows the adsorption capacity of commercial carbon, Carbon X, AC-AP, and AC-Si; and

[0057] FIG. 10 shows the viability of human cell lines for Carbon-X, AC-AP, and AC-Si. DETAILED DESCRIPTION

[0058] The present invention is based on the understanding that current methods for converting low-grade carbon into high-value end products are energy intensive and require harsh chemicals. In this regard, downstream processing is extremely challenging and not suitable for large-scale manufacturing. To this end, the inventors have developed a method for converting carbon black waste, such as produced from refinery waste, into activated carbon.

[0059] In the present invention, a method for obtaining highly efficient activated carbon by combining physical and chemical activation methods is developed. In this regard, a synergistic effect can be obtained in that less (or non) dangerous chemicals can be used. In addition, a lower activation temperature can be used, which, when combined with chemicals, provides activated carbon with high surface area, pore size and adsorption distribution. Advantageously, such a method can be cost-effective because 50% less energy can be used and a higher yield of 40% can be obtained. Further advantageously, since the method uses waste carbon, production costs can be reduced. Compared with current industrial practices, the method is also more environmentally friendly.

[0060] Therefore, the present invention relates to a method for forming activated carbon, comprising:

[0061] a) mixing carbon black with an activated catalyst in a polar solvent to form a mixture; and

[0062] b) heating the mixture at about 350° C. to about 500° C. to form activated carbon;

[0063] wherein the weight ratio of carbon black to activated catalyst is from about 1:0.1 to about 1:0.5; and

[0064] The activating catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate, acetic acid, ammonia, or a combination thereof.

[0065] The process of forming activated carbon converts carbon black into activated carbon. 'Activated carbon', also known as activated charcoal, is considered "activated" when it is characterized by an increased surface area. For example, the surface area of ​​1 gram of activated carbon can be about 500 m 2 About 3,000m 2 . In this regard, the increase in surface area from charcoal to activated carbon is produced by a process that creates many pores and cracks in the charcoal. These pores can be used for adsorption, interaction with halogens, acid-base reactions, or redox reactions. Conventionally, activated carbon is produced by physical activation, in which the charcoal is carbonized (usually pyrolyzed at a temperature in the range of 600-900°C in an inactive atmosphere such as argon or nitrogen), or oxidized at high temperature (exposed to an oxidizing atmosphere (oxygen or steam) at a temperature of 600-1200°C). Alternatively, the activation chemicals are traditionally strong acids or bases (phosphoric acid 25%, potassium hydroxide 5%, sodium hydroxide 5%), followed by heating at a temperature of about 250-600°C. It is believed that at this stage, the temperature activates the carbon by forcing the material to open up and have more micropores. Activated is sometimes replaced by active.

[0066] In contrast, the present invention relies on an activating catalyst or oxidant, such as ammonium persulfate, sodium persulfate, potassium persulfate, acetic acid, ammonia, or a combination thereof to activate the carbon. Such compounds are less harsh than strong acids and bases. In addition, compounds such as ammonium persulfate, sodium persulfate, and potassium persulfate are solids and are therefore easier to handle on a large scale.

[0067] The activated carbon of the present invention is formed as a nanoporous material. "Nanoporous" refers to an organic or inorganic framework that supports a porous structure. The size of the pores is generally less than 100 nm. The pores can be filled with a fluid (liquid or gas). As described by the International Union of Pure and Applied Chemistry (IUPAC), nanoporous materials can be subdivided into three categories: microporous materials having pores of about 0.2 to about 2 nm; mesoporous materials having pores of about 2 to about 50 nm; and macroporous materials having pores greater than about 50 nm. Surface area measurements can be related to the presence of micropores, mesopores, and macropores, while iodine values ​​can be related to the presence of micropores.

[0068] In some embodiments, the carbon black is Carbon X (a product of Sembcorp Industries Ltd). Carbon X is a carbon black obtained from carbon waste using an acid or base leaching process.

[0069] Carbon black is mixed with an activation catalyst in a polar solvent to form a mixture. As used herein, "activation catalyst" refers to a substance that is at least partially used to activate carbon black by, for example, initiating a chemical reaction on the surface of carbon black. As a result, the reaction rate can be increased. Alternatively, the activation catalyst can also be referred to as an oxidant or reagent. The activation catalyst can be added in small amounts relative to carbon black. In some embodiments, the activation catalyst is a homogeneous catalyst that can decompose at a specific temperature. The activation catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate, acetic acid or ammonia. In some embodiments, the activation catalyst is ammonium persulfate. In particular, the inventors have found that, for example, ammonium persulfate, sodium persulfate and potassium persulfate are advantageous because they are not as harsh as other chemicals used in chemical oxidation methods. In addition, persulfate can be used as an etchant to remove impurities on the surface of carbon black, thereby exposing the carbon black surface to activation. At the end of the reaction, persulfate can be converted into sulfate and easily removed.

[0070] In some embodiments, the weight ratio of carbon black to activated catalyst is from about 1:0.1 to about 1:0.5. In other embodiments, the weight ratio is from about 1:0.1 to about 1:0.4, from about 1:0.1 to about 1:0.3, or from about 1:0.1 to about 1:0.2. In other embodiments, the weight ratio is about 1:0.1, about 1:0.2, about 1:0.3, about 1:0.4, or about 1:0.5.

[0071] When the weight ratio is less than 1:0.1, the activation catalyst is not sufficiently activated to generate porosity in the carbon, which results in a low surface area. When the weight ratio is higher than 1:0.5, the excess activation catalyst will destroy the pores by uncontrollable activation of persulfate. It is found that the weight ratio within the range is conducive to obtaining uniform porous properties to reach about 800 m2 / g of surface area.

[0072] As used herein, 'polar solvents' refer to solvents that have molecules that have a slight charge due to their shape. For example, water is a molecule with one oxygen atom and two hydrogen atoms. The two hydrogen atoms are not on opposite sides of the oxygen, but at an angle. Also within its scope are polar protic solvents and polar aprotic solvents. A protic solvent is a solvent that has hydrogen atoms bonded to oxygen (such as in hydroxyl groups), nitrogen (such as in amine groups), or fluoride (such as hydrogen fluoride). In general, any solvent containing reactive H + Solvents that are protic are called protic solvents. The molecules of such solvents usually easily transfer protons (H + ) is provided to the solute. Water is the most common protic solvent. In contrast, aprotic solvents cannot provide hydrogen. Solvent system refers to the combination of solvents that obtain the final single phase, and is included in this definition. Both 'solvent' and 'solvent system' may include, but are not limited to, pentane, cyclopentane, hexane, cyclohexane, benzene, toluene, dioxane, chloroform, diethyl ether, dichloromethane, tetrahydrofuran, ethyl acetate, acetone, dimethylformamide, acetonitrile, dimethyl sulfoxide, nitromethane, propylene carbonate, formic acid, butanol, isopropanol, propanol, ethanol, methanol, acetic acid, ethylene glycol, diethylene glycol or water. Aqueous solvents or solvent systems may also include dissolved ions, salts and molecules, such as amino acids, proteins, sugars and phospholipids. These salts can be, but are not limited to, sodium chloride, potassium chloride, ammonium acetate, magnesium acetate, magnesium chloride, magnesium sulfate, potassium acetate, potassium chloride, sodium acetate, sodium citrate, zinc chloride, HEPES sodium, calcium chloride, ferric nitrate, sodium bicarbonate, potassium phosphate and sodium phosphate.

[0073] In some embodiments, the solvent is selected from water, ethanol, ethylene glycol, or a combination thereof. In other embodiments, the solvent is water. The use of green solvents such as water allows for convenient processing of production media and disposal and removal of waste materials.

[0074] In some embodiments, the weight ratio of carbon black to solvent is from about 1:5 to about 1:100. In other embodiments, the weight ratio is from about 1:5 to about 1:90, from about 1:5 to about 1:80, from about 1:5 to about 1:70, from about 1:5 to about 1:60, from about 1:5 to about 1:50, from about 1:5 to about 1:40, from about 1:5 to about 1:30, from about 1:5 to about 1:20, or from about 1:5 to about 1:10. In other embodiments, the weight ratio is about 1:5, 1:10, 1:20; 1:30, 1:40; 1:50, 1:60; 1:70, 1:80; 1:90, or 1:100.

[0075] In some embodiments, the mixture is mixed for at least 1 hour. In other embodiments, the mixture is mixed for at least 2 hours, 3 hours, 4 hours, or 5 hours. Mixing allows for uniform dispersion.

[0076] In some embodiments, the method of forming activated carbon comprises:

[0077] a) mixing carbon black with an activated catalyst in a polar solvent to form a mixture; and

[0078] b) heating the mixture at about 350° C. to about 500° C. to form activated carbon;

[0079] wherein the weight ratio of carbon black to activated catalyst is from about 1:0.1 to about 1:0.5; and

[0080] The activating catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate, or a combination thereof.

[0081] In some embodiments, the method further comprises adding a cocatalyst to the mixture. A cocatalyst refers to a substance or reagent that produces a catalytic effect together with one or more other catalysts. A cocatalyst can provide active sites for surface catalytic reactions; the chemical properties (structure, type, position, etc.) of the cocatalyst affect the behavior of the surface reaction. In this regard, it can be a heterogeneous cocatalyst. Alternatively, the cocatalyst can be a homogeneous chemical species that improves catalytic activity.

[0082] In some embodiments, the promoter is ammonia or ammonium hydroxide.

[0083] In some embodiments, the co-catalyst is mixed with the mixture for at least 1 h. In other embodiments, the co-catalyst is mixed with the mixture for at least 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, or 5 h.

[0084] In some embodiments, the weight ratio of the activated catalyst to the co-catalyst is about 1:0.1. In other embodiments, the weight ratio is about 1:0.05, 1:0.07, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, or 1:0.5.

[0085] In some embodiments, the pH of the mixture is maintained at about 7 to about 9.

[0086] In some embodiments, the mixture is heated at a temperature of about 150° C. to about 500° C. In other embodiments, the mixture is heated at a temperature of about 200° C. to about 500° C., about 250° C. to about 500° C., about 300° C. to about 500° C., about 350° C. to about 500° C., or about 400° C. to about 500° C.

[0087] In some embodiments, the mixture is heated to less than 490° C. In other embodiments, the mixture is heated to less than 480° C., 470° C., 460° C., 450° C., 440° C., 430° C., 420° C., 410° C., or 400° C. In other embodiments, the mixture is heated to about 490° C., 480° C., 470° C., 460° C., 450° C., 440° C., 430° C., 420° C., 410° C., 400° C., 350° C., 300° C., 250° C., or 200° C. In other embodiments, the mixture is heated from about 200°C to about 500°C, from about 250°C to about 500°C, from about 300°C to about 500°C, from about 350°C to about 500°C, from about 370°C to about 500°C, from about 400°C to about 500°C, from about 420°C to about 500°C, from about 440°C to about 500°C, from about 460°C to about 500°C, or from about 480°C to about 500°C.

[0088] In some embodiments, the mixture is heated at a rate of about 1°C / min to about 5°C / min. In other embodiments, the mixture is heated at a rate of about 1°C / min to about 4°C / min or about 2°C / min to about 4°C / min.

[0089] In some embodiments, the mixture is heated at about 400° C. for at least 3 hours to form activated carbon. In other embodiments, the mixture is heated for at least 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, or 6 hours.

[0090] Advantageously, this temperature is lower than that used in the prior art and, therefore, may be more suitable for large-scale manufacturing. In addition, in combination with an activation catalyst, the activation catalyst may be activated to produce uniform pores and ultimately decomposed for easy removal. This provides a product that is superior (or at least has the same performance) as commercially available activated carbon.

[0091] In some embodiments, the method further comprises a step of drying the mixture after step (a). In the preparation of the heating step, the step of drying the mixture is to remove the solvent. In this regard, there is no solvent in the mixture before the heating step. This is advantageous because pressurization and / or a closed system are not required in the method. Therefore, the energy consumption and safety requirements when manufacturing activated carbon are lower than other commercial products. Drying can occur at about 100°C. In other embodiments, drying is performed at about 80°C, about 90°C, about 100°C, about 110°C, about 120°C, about 130°C or about 140°C. In other embodiments, the mixture is dried for about 1h, about 2h, about 3h, about 4h, about 5h, about 6h, about 7h, about 8h, about 10h, about 12h or about 24h.

[0092] In some embodiments, the step of drying the mixture is performed by filtering the mixture through a filter and collecting the solids. In other embodiments, the mixture is dried by evaporating the solvent. For example, if water is used, the mixture can be dried at a temperature greater than about 100° C. for at least about 1 h.

[0093] In some embodiments, after heating the mixture to form the activated carbon, the activated carbon is subjected to a purification step. The purification step may include washing with water, filtering, and drying the activated carbon.

[0094] Thus, in some embodiments, the method of forming activated carbon comprises:

[0095] a) mixing carbon black with an activated catalyst in a polar solvent to form a mixture; and

[0096] b) drying the mixture in step (a) to form a solid;

[0097] c) heating the solid from step (b) at about 350° C. to about 500° C. to form activated carbon;

[0098] wherein the weight ratio of carbon black to activated catalyst is from about 1:0.1 to about 1:0.5; and

[0099] The activating catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate, or a combination thereof.

[0100] In some embodiments, the method comprises:

[0101] a) mixing carbon black with an activated catalyst in a polar solvent to form a mixture; and

[0102] b) heating the mixture at about 400° C. for at least 3 hours to form activated carbon;

[0103] wherein the weight ratio of carbon black to activated catalyst is about 1:0.2; and

[0104] The activating catalyst is selected from ammonium persulfate.

[0105] In some embodiments, the method comprises:

[0106] a) mixing carbon black with an activated catalyst in a polar solvent to form a mixture; and

[0107] b) drying the mixture in step (a) to form a solid;

[0108] c) heating the solid from step (b) at about 400° C. to form activated carbon;

[0109] wherein the weight ratio of carbon black to activated catalyst is about 1:0.2; and

[0110] The activating catalyst is selected from ammonium persulfate.

[0111] In some embodiments, the method comprises:

[0112] a) mixing carbon black with an activated catalyst in a polar solvent to form a mixture; and

[0113] b) heating the mixture at about 400° C. for at least 3 hours to form activated carbon;

[0114] wherein the weight ratio of carbon black to activated catalyst is about 1:0.2; and

[0115] wherein the activating catalyst is selected from ammonium persulfate;

[0116] wherein the mixture further comprises ammonia as a co-catalyst;

[0117] wherein the weight ratio of the activated catalyst to the co-catalyst is about 1:0.1; and

[0118] The pH of the mixture is maintained at about 7 to about 9.

[0119] In some embodiments, the method comprises:

[0120] a) mixing carbon black with an activated catalyst in a polar solvent to form a mixture; and

[0121] b) drying the mixture in step (a) to form a solid;

[0122] c) heating the solid from step (b) at about 400° C. for at least 3 hours to form activated carbon;

[0123] wherein the weight ratio of carbon black to activated catalyst is about 1:0.2; and

[0124] wherein the activating catalyst is selected from ammonium persulfate;

[0125] wherein the mixture further comprises ammonia as a co-catalyst;

[0126] wherein the weight ratio of the activated catalyst to the co-catalyst is about 1:0.1; and

[0127] The pH of the mixture is maintained at about 7 to about 9.

[0128] The activated carbon formed is nanoporous in nature. In particular, the activated carbon is microporous and mesoporous. In this regard, the size of the pores can be from about 0.2 to about 50 nm.

[0129] For example, Table 2 shows an example of activated carbon with a pore size of 1.53 nm. In some embodiments, the activated carbon has a micropore ratio of about 40% to about 99% relative to the total porosity. In other embodiments, the micropore ratio is about 45% to about 99%, about 50% to about 99%, about 55% to about 99%, about 60% to about 99%, about 65% to about 99%, about 70% to about 99%, about 75% to about 99%, about 80% to about 99%, about 85% to about 99%, about 90% to about 99%, about 91% to about 99%, about 92% to about 99%, about 93% to about 99%, about 94% to about 99%, or about 95% to about 99%. In other embodiments, the micropore ratio is about 50% to about 99%, about 50% to about 85%, about 50% to about 80%, about 50% to about 75%, about 50% to about 70%, about 50% to about 65%, about 50% to about 60%, or about 50% to about 55%. The micropore ratio can be obtained, for example, by comparing the iodine value and the BET surface area of ​​the activated carbon.

[0130] The method may further include the step of silane functionalizing the carbon black to form a silane functionalized activated carbon. Advantageously, the inventors have found that better uniformity and higher functionalization ratios can be obtained by introducing silane functional groups on the carbon black and then subjecting the carbon black to a heating step rather than introducing silane functional groups directly on the activated carbon. In addition, the heating procedure triggers pore formation, which increases textural properties such as surface area and pore radius.

[0131] Advantageously, the silane agent acts as a bridging moiety in forming mesoporous activated carbon. To this end, the silane agent allows the formation of inter-carbon connections between carbon particles, thereby forming pores between the carbon particles.

[0132] Thus, in some embodiments, the method comprises:

[0133] ai) mixing carbon black with a silane agent;

[0134] a) mixing the mixture from step (ai) with an activated catalyst in a polar solvent to form a mixture; and

[0135] b) heating the mixture at about 350° C. to about 500° C. to form activated carbon;

[0136] wherein the weight ratio of carbon black to activated catalyst is from about 1:0.1 to about 1:0.5;

[0137] The activating catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate, acetic acid, ammonia, or a combination thereof.

[0138] In some embodiments, the silane agent is selected from bistriethoxysilane (1,2-bis(triethoxysilyl)ethane), 1,2-bis(trichlorosilyl)ethane, 1,2-bis(trimethoxysilyl)ethane, or a combination thereof. In other embodiments, the silane agent is bistriethoxysilane (1,2-bis(triethoxysilyl)ethane).

[0139] In some embodiments, the weight ratio of carbon black to silane agent is about 1:0.25. In other embodiments, the weight ratio is about 1:0.15, 1:0.2, 1:0.3, 1:0.35, or 1:0.4. In some embodiments, the weight ratio of carbon black to silane agent is about 1:0.18 to about 1:0.25. In other embodiments, the weight ratio is about 1:0.19 to about 1:0.25, about 1:0.20 to about 1:0.25, about 1:0.21 to about 1:0.25, about 1:0.22 to about 1:0.25, or about 1:0.23 to about 1:0.25.

[0140] In some embodiments, the mixture is stirred for at least 1 hour with the addition of the silane agent. This allows the silane agent to react with the carbon black. In other embodiments, the mixture is stirred for at least 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 6 hours, 8 hours, 12 hours, or 24 hours.

[0141] In some embodiments, the mixture is stirred at room temperature with the addition of the silane agent. In other embodiments, the mixture is stirred at about 15°C, 20°C, 25°C, 35°C, or 40°C.

[0142] In some embodiments, a silanization catalyst is added with the silane agent. In some embodiments, the activating catalyst is acetic acid and / or ammonia. Other catalysts suitable for silanization may also be used. It has been found that milder catalysts are advantageous for promoting silane functionalization.

[0143] In some embodiments, the weight ratio of the silane agent to the catalyst is about 1:0.5. In other embodiments, the weight ratio is 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, or 1:1.7. In some embodiments, the weight ratio of the silane agent to the catalyst is about 1:0.5 to about 1:1.7. In other embodiments, the weight ratio is from about 1:0.5 to about 1:1.6, from about 1:0.5 to about 1:1.5, from about 1:0.5 to about 1:1.4, from about 1:0.5 to about 1:1.3, from about 1:0.5 to about 1:1.2, from about 1:0.5 to about 1:1.1, from about 1:0.5 to about 1:1.0, from about 1:0.5 to about 1:0.9, from about 1:0.5 to about 1:0.8, from about 1:0.5 to about 1:0.7, or from about 1:0.5 to about 1:0.6.

[0144] To promote the dispersion of the silanized carbon black, a polar solvent system can be used. In some embodiments, the solvent is a mixture of water and ethanol in a weight ratio of 85:15, a mixture of water and ethylene glycol in a weight ratio of 85:15, or a mixture of ethanol and ethylene glycol in a weight ratio of 85:15. Other combinations of these solvents can also be used, depending on the amount of silane agent and / or the amount of carbon black added.

[0145] In some embodiments, the mixture is heated at about 350° C. for at least 6 hours to form the silane-functionalized activated carbon. In other embodiments, the mixture is heated at greater than 350° C. In other embodiments, the mixture is heated at about 400° C. for at least 3 hours.

[0146] In some embodiments, the method further comprises a step of drying the mixture after step (ai). In the preparation of mixing the silanized carbon black with the activated catalyst, the step of drying the mixture is to remove the solvent. This also allows the change of polar solvents. In this regard, there is no solvent in the mixture before the mixing step with the activated catalyst. Drying can occur at about 100°C. In other embodiments, drying is performed at about 80°C, about 90°C, about 100°C, about 110°C, about 120°C, about 130°C or about 140°C. In other embodiments, the mixture is dried for about 1h, about 2h, about 3h, about 4h, about 5h, about 6h, about 7h, about 8h, about 10h, about 12h or about 24h.

[0147] In some embodiments, the step of drying the mixture is performed by filtering the mixture through a filter and collecting the solids. In other embodiments, the mixture is dried by evaporating the solvent. For example, if water and / or ethanol are used, the mixture can be dried at a temperature greater than about 100° C. for at least about 1 h.

[0148] The silanized activated carbon formed is nanoporous in nature. In particular, the silanized activated carbon is microporous and mesoporous. In this regard, the size of the pores is from about 0.2 to about 50 nm.

[0149] In some embodiments, the method comprises:

[0150] ai) mixing carbon black with a silane agent;

[0151] a) mixing the mixture from step (ai) with an activated catalyst in a polar solvent to form a mixture; and

[0152] b) heating the mixture at about 350° C. to about 500° C. to form activated carbon;

[0153] wherein the weight ratio of carbon black to activated catalyst is from about 1:0.1 to about 1:0.5;

[0154] The activating catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate, or a combination thereof.

[0155] In some embodiments, the method comprises:

[0156] ai) mixing carbon black with a silane agent and a catalyst;

[0157] a) mixing the mixture from step (ai) with an activated catalyst in a polar solvent to form a mixture; and

[0158] b) heating the mixture at about 350° C. to about 500° C. to form activated carbon;

[0159] wherein the weight ratio of carbon black to activated catalyst is from about 1:0.1 to about 1:0.5;

[0160] wherein the catalyst is acetic acid and / or ammonia; and

[0161] The activating catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate, or a combination thereof.

[0162] In some embodiments, the method comprises:

[0163] ai) mixing carbon black with a silane agent and a catalyst;

[0164] a) mixing the mixture from step (ai) with an activated catalyst in a polar solvent to form a mixture; and

[0165] b) heating the mixture at about 350° C. to about 500° C. to form activated carbon;

[0166] wherein the weight ratio of carbon black to activated catalyst is from about 1:0.1 to about 1:0.5;

[0167] wherein the silane agent is selected from bistriethoxysilane (1,2-bis(triethoxysilyl)ethane), 1,2-bis(trichlorosilyl)ethane, 1,2-bis(trimethoxysilyl)ethane, or a combination thereof;

[0168] wherein the catalyst is acetic acid and / or ammonia; and

[0169] The activating catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate, or a combination thereof.

[0170] In some embodiments, the method comprises:

[0171] ai) mixing carbon black with a silane agent and a catalyst;

[0172] a) mixing the mixture from step (ai) with an activated catalyst in a polar solvent to form a mixture; and

[0173] b) heating the mixture at about 350° C. to about 500° C. to form activated carbon;

[0174] wherein the weight ratio of carbon black to activated catalyst is from about 1:0.1 to about 1:0.5;

[0175] wherein the silane agent is selected from bistriethoxysilane (1,2-bis(triethoxysilyl)ethane), 1,2-bis(trichlorosilyl)ethane, 1,2-bis(trimethoxysilyl)ethane, or a combination thereof;

[0176] Wherein the catalyst is acetic acid and / or ammonia;

[0177] wherein the activating catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate, or a combination thereof; and

[0178] The weight ratio of carbon black to silane agent is about 1:0.25.

[0179] In some embodiments, the method comprises:

[0180] ai) mixing carbon black with a silane agent and a catalyst;

[0181] aii) drying the mixture in step (ai) to form a solid;

[0182] a) mixing the solid from step (aii) with an activated catalyst in a polar solvent to form a mixture; and

[0183] b) heating the mixture at about 350° C. to about 500° C. to form activated carbon;

[0184] wherein the weight ratio of carbon black to activated catalyst is from about 1:0.1 to about 1:0.5;

[0185] wherein the catalyst is acetic acid and / or ammonia; and

[0186] The activating catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate, or a combination thereof.

[0187] In some embodiments, the method comprises:

[0188] ai) mixing carbon black with a silane agent and a catalyst;

[0189] aii) drying the mixture in step (ai) to form a first solid;

[0190] a) mixing the solid from step (aii) with an activated catalyst in a polar solvent to form a mixture;

[0191] b) drying the mixture of step (a) to form a second solid; and

[0192] c) heating the second solid at about 350° C. to about 500° C. to form activated carbon;

[0193] wherein the weight ratio of carbon black to activated catalyst is from about 1:0.1 to about 1:0.5;

[0194] wherein the catalyst is acetic acid and / or ammonia; and

[0195] The activating catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate, or a combination thereof.

[0196] In some embodiments, the method comprises:

[0197] ai) mixing carbon black with a silane agent and a catalyst;

[0198] aii) drying the mixture in step (ai) to form a first solid;

[0199] a) mixing the solid from step (aii) with an activated catalyst in a polar solvent to form a mixture;

[0200] b) drying the mixture of step (a) to form a second solid; and

[0201] c) heating the second solid at about 350° C. to about 500° C. to form activated carbon;

[0202] wherein the weight ratio of carbon black to activated catalyst is about 1:0.2;

[0203] wherein the catalyst is acetic acid and / or ammonia; and

[0204] The activating catalyst is ammonium persulfate.

[0205] The inventors have also found that, by reacting with a silane agent, an activated carbon having a higher ratio of mesopores relative to micropores can be formed. These mesoporous activated carbons have pores of about 2 to about 50 nm. This can be obtained by mixing carbon black, a silane agent and an activation catalyst together in a polar solvent and then heating the mixture. The silane agent is used as a bridging portion for forming mesoporous activated carbon. For this reason, the silane agent allows the formation of carbon-to-carbon connections between carbon particles, thereby forming additional mesopores between carbon particles. Advantageously, this increases the amount of mesopores (relative to micropores) and therefore increases the surface area.

[0206] In some embodiments, the carbon black, silane agent, and activating catalyst are added in one step.

[0207] Therefore, the present invention also provides a method for forming silane-functionalized activated carbon, which comprises:

[0208] a) mixing carbon black with an activated catalyst in a polar solvent to form a mixture; and

[0209] b) heating the mixture at about 350° C. to about 500° C. to form activated carbon;

[0210] wherein the weight ratio of carbon black to activated catalyst is from about 1:0.1 to about 1:0.5;

[0211] wherein the activating catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate, acetic acid, ammonia, or a combination thereof; and

[0212] Wherein the mixing step (step (a)) further comprises a silane agent.

[0213] In some embodiments, the method comprises:

[0214] a) mixing carbon black with an activated catalyst in a polar solvent to form a mixture; and

[0215] b) drying the mixture in step (a) to form a solid;

[0216] c) heating the solid at about 350° C. to about 500° C. to form activated carbon;

[0217] wherein the weight ratio of carbon black to activated catalyst is from about 1:0.1 to about 1:0.5;

[0218] wherein the activating catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate, acetic acid, ammonia, or a combination thereof; and

[0219] Wherein the mixing step (step (a)) further comprises a silane agent.

[0220] In some embodiments, the method comprises:

[0221] a) mixing carbon black with an activated catalyst in a polar solvent to form a mixture; and

[0222] b) heating the mixture at about 350° C. to about 500° C. to form activated carbon;

[0223] wherein the weight ratio of carbon black to activated catalyst is from about 1:0.1 to about 1:0.5;

[0224] wherein the activating catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate, acetic acid, ammonia, or a combination thereof;

[0225] wherein the mixing step (step (a)) further comprises bistriethoxysilane as a silane agent; and

[0226] The weight ratio of carbon black to silane agent is about 1:0.25.

[0227] In some embodiments, the method comprises:

[0228] a) mixing carbon black with an activated catalyst in a polar solvent to form a mixture; and

[0229] b) drying the mixture in step (a) to form a solid;

[0230] c) heating the solid at about 350° C. to about 500° C. to form activated carbon;

[0231] wherein the weight ratio of carbon black to activated catalyst is from about 1:0.1 to about 1:0.5;

[0232] wherein the activating catalyst is selected from ammonium persulfate, sodium persulfate, potassium persulfate, acetic acid, ammonia, or a combination thereof;

[0233] wherein the mixing step (step (a)) further comprises bistriethoxysilane as a silane agent; and

[0234] The weight ratio of carbon black to silane agent is about 1:0.25.

[0235] In some embodiments, the method comprises:

[0236] a) mixing carbon black with an activated catalyst in a polar solvent to form a mixture; and

[0237] b) heating the mixture at about 400° C. to form activated carbon;

[0238] wherein the weight ratio of carbon black to activated catalyst is about 1:0.1;

[0239] Wherein the activated catalyst is acetic acid and / or ammonia;

[0240] wherein the mixing step (step (a)) further comprises bistriethoxysilane as a silane agent;

[0241] wherein the weight ratio of carbon black to silane agent is about 1:0.25; and

[0242] The weight ratio of the silane agent to the catalyst is about 1:0.5.

[0243] Advantageously, due to the increased amount of mesopores and therefore the increased surface area, chemical activation using persulfate (although more advantageous) was found to be unnecessary for applications such as petroleum waste adsorption.

[0244] For example, Table 2 shows an example of a silanized activated carbon having a pore size of 9.02 nm. In some embodiments, the silanized activated carbon has a micropore ratio of about 10% to about 50% relative to the total porosity. In other embodiments, the micropore ratio is about 15% to about 50%, about 20% to about 50%, about 15% to about 50%, about 25% to about 50%, about 30% to about 50%, about 35% to about 50%, about 40% to about 50%, or about 45% to about 50%. The micropore ratio can be obtained, for example, by comparing the iodine value and the BET surface area of ​​the activated carbon.

[0245] In some embodiments, the method comprises:

[0246] a) mixing carbon black with an activated catalyst in a polar solvent to form a mixture; and

[0247] b) drying the mixture in step (a) to form a solid;

[0248] c) heating the solid at about 400° C. to form activated carbon;

[0249] wherein the weight ratio of carbon black to activated catalyst is about 1:0.1;

[0250] Wherein the activated catalyst is acetic acid and / or ammonia;

[0251] wherein the mixing step (step (a)) further comprises bistriethoxysilane as a silane agent;

[0252] wherein the weight ratio of carbon black to silane agent is about 1:0.25; and

[0253] The weight ratio of the silane agent to the catalyst is about 1:0.5.

[0254] In some embodiments, the method of forming a silane-functionalized activated carbon comprises:

[0255] a) mixing carbon black with a silane agent and an activating catalyst in a polar solvent to form a mixture; and

[0256] b) heating the mixture at about 350° C. to about 500° C. to form a silane-functionalized activated carbon;

[0257] wherein the weight ratio of carbon black to activating catalyst is from about 1:0.1 to about 1:0.5; and wherein the activating catalyst is selected from acetic acid or ammonia.

[0258] In some embodiments, the method of forming a silane-functionalized activated carbon comprises:

[0259] a) mixing carbon black with a silane agent and an activating catalyst in a polar solvent to form a mixture; and

[0260] b) drying the mixture in step (a) to form a solid;

[0261] c) heating the solid at about 350° C. to about 500° C. to form a silane-functionalized activated carbon;

[0262] wherein the weight ratio of carbon black to activating catalyst is from about 1:0.1 to about 1:0.5; and wherein the activating catalyst is selected from acetic acid or ammonia.

[0263] In some embodiments, the method of forming a silane-functionalized activated carbon comprises:

[0264] a) mixing carbon black with a silane agent and an activating catalyst in a polar solvent to form a mixture; and

[0265] b) heating the mixture at about 400° C. to form a silane-functionalized activated carbon;

[0266] wherein the weight ratio of carbon black to activated catalyst is about 1:0.1; and

[0267] The activated catalyst is acetic acid.

[0268] In some embodiments, the method of forming a silane-functionalized activated carbon comprises:

[0269] a) mixing carbon black with a silane agent and an activating catalyst in a polar solvent to form a mixture; and

[0270] b) drying the mixture in step (a) to form a solid;

[0271] c) heating the solid at about 400° C. to form a silane-functionalized activated carbon;

[0272] wherein the weight ratio of carbon black to activated catalyst is about 1:0.1; and

[0273] The activated catalyst is acetic acid.

[0274] In some embodiments, the method of forming a silane-functionalized activated carbon comprises:

[0275] a) mixing carbon black with a silane agent and an activating catalyst in a polar solvent to form a mixture; and

[0276] b) heating the mixture at about 400° C. to form a silane-functionalized activated carbon;

[0277] wherein the weight ratio of carbon black to activated catalyst is about 1:0.1; wherein the activated catalyst is acetic acid;

[0278] wherein the silane agent is bistriethoxysilane; and

[0279] The weight ratio of carbon black to silane agent is about 1:0.25.

[0280] In some embodiments, the method of forming a silane-functionalized activated carbon comprises:

[0281] a) mixing carbon black with a silane agent and an activating catalyst in a polar solvent to form a mixture; and

[0282] b) drying the mixture in step (a) to form a solid;

[0283] c) heating the solid at about 400° C. to form a silane-functionalized activated carbon;

[0284] wherein the weight ratio of carbon black to activated catalyst is about 1:0.1; wherein the activated catalyst is acetic acid;

[0285] wherein the silane agent is bistriethoxysilane; and

[0286] The weight ratio of carbon black to silane agent is about 1:0.25.

[0287] In some embodiments, the method of forming a silane-functionalized activated carbon comprises:

[0288] a) mixing carbon black with a silane agent and an activating catalyst in a polar solvent to form a mixture; and

[0289] b) heating the mixture at about 400° C. to form a silane-functionalized activated carbon;

[0290] wherein the weight ratio of carbon black to activated catalyst is about 1:0.1; wherein the activated catalyst is acetic acid;

[0291] The silane agent is bistriethoxysilane;

[0292] wherein the weight ratio of carbon black to silane agent is about 1:0.25; and

[0293] The weight ratio of the silane agent to the catalyst is about 1:0.5.

[0294] In some embodiments, the method of forming a silane-functionalized activated carbon comprises:

[0295] a) mixing carbon black with a silane agent and an activating catalyst in a polar solvent to form a mixture; and

[0296] b) drying the mixture in step (a) to form a solid;

[0297] c) heating the solid at about 400° C. to form a silane-functionalized activated carbon;

[0298] wherein the weight ratio of carbon black to activated catalyst is about 1:0.1; wherein the activated catalyst is acetic acid;

[0299] The silane agent is bistriethoxysilane;

[0300] wherein the weight ratio of carbon black to silane agent is about 1:0.25; and

[0301] The weight ratio of the silane agent to the catalyst is about 1:0.5.

[0302] The present invention also relates to activated carbon formed by the methods disclosed herein.The particle size of the activated carbon may be from about 40 nm to about 80 nm.

[0303] In other embodiments, when microporous and mesoporous activated carbon is formed, the pore size is from about 0.2nm to about 50nm, from about 0.5nm to about 50nm, from about 1nm to about 50nm, from about 1nm to about 45nm, from about 1nm to about 40nm, from about 1nm to about 35nm, or from about 1nm to about 30nm. In other embodiments, when microporous and mesoporous activated carbon is formed, the pore size is from about 0.2nm to about 40nm, from about 0.2nm to about 30nm, from about 0.2nm to about 20nm, from about 0.2nm to about 10nm, from about 0.2nm to about 8nm, from about 0.2nm to about 6nm, from about 0.2nm to about 5nm, from about 0.2nm to about 4nm, from about 0.2nm to about 3nm, or from about 0.2nm to about 2nm.

[0304] In other embodiments, when forming microporous and mesoporous activated carbon (or silanized activated carbon), the pore size is about 2nm to about 50nm, about 5nm to about 50nm, about 10nm to about 50nm, about 15nm to about 50nm, about 20nm to about 50nm, about 25nm to about 50nm, about 30nm to about 50nm, about 35nm to about 50nm, or about 40nm to about 50nm. In other embodiments, when forming microporous and mesoporous activated carbon, the pore size is about 2nm to about 40nm, about 2nm to about 30nm, about 2nm to about 20nm, or about 2nm to about 10nm.

[0305] The present invention also provides activated carbon as disclosed herein. The particle size of the activated carbon may be from about 40 nm to about 80 nm. The BET surface area of ​​the activated carbon may be greater than 600 m 2 / g.

[0306] In some embodiments, the activated carbon is silane functionalized. In other embodiments, the activated carbon is silane functionalized with triethoxysilane.

[0307] The present invention also provides a silane-functionalized activated carbon as disclosed herein. The particle size of the silane-functionalized activated carbon may be from about 40 nm to about 80 nm. The BET surface area of ​​the silane-functionalized activated carbon may be greater than 600 m 2 / g.

[0308] The present invention also provides silane-functionalized activated carbon as disclosed herein. In some embodiments, the particle size of the activated carbon is from about 140 nm to about 500 nm. In some embodiments, the BET surface area of ​​the silane-functionalized activated carbon is greater than 600 m 2 / g.

[0309] In some embodiments, the silane-functionalized activated carbon includes at least 4 carbon particles.

[0310] In some embodiments, the silane-functionalized activated carbon has a silica shell having a thickness of about 10 nm on at least the surface of the activated carbon. In other embodiments, the thickness is about 15 nm or 20 nm.

[0311] In some embodiments, the pore size of the silane-functionalized activated carbon is at least 9 nm.

[0312] The synthesized activated carbon (or silane-functionalized activated carbon) showed higher adsorption capacity compared to low-grade carbon extracted from carbon black waste and commercial carbon through adsorption studies on rhodamine B, arsenate, and selenate.

[0313] In some embodiments, the BET surface area of ​​the activated carbon (or silane-functionalized activated carbon) is greater than 600 m 2In other embodiments, the BET surface area is greater than 650 m 2 / g、700m 2 / g, 750m 2 / g or 800m 2 In other embodiments, the BET surface area is about 600 m 2 / g, about 650m 2 / g, about 700m 2 / g, about 750m 2 / g or about 800m 2 In other embodiments, the BET surface area is about 600 m 2 / g to about 1500m 2 / g, about 600m 2 / g to about 1400m 2 / g, about 600m 2 / g to about 1300m 2 / g, about 600m 2 / g to about 1200m 2 / g, about 600m 2 / g to about 1100m 2 / g, about 600m 2 / g to about 1000m 2 / g, about 600m 2 / g to about 900m 2 / g, or about 600m 2 / g to about 800m 2 / g.

[0314] In some embodiments, the total pore volume of the activated carbon (or silane-functionalized activated carbon) is greater than 0.8 cm 3 In other embodiments, the total pore volume is greater than 0.85 cm 3 / g, 0.9cm 3 / g, 1cm 3 / g, 1.1cm 3 / g, 1.2cm 3 / g, 1.25cm 3 / g, 1.3cm 3 / g, 1.35cm 3 / g, 1.4cm 3 / g, 1.45cm 3 / g or 1.5cm 3 In other embodiments, the total pore volume is about 0.85 cm 3 / g, 0.9cm 3 / g, 1cm 3 / g, 1.1cm 3 / g, 1.2cm 3 / g, 1.25cm 3 / g, 1.3cm 3 / g, 1.35cm 3 / g, 1.4cm 3 / g, 1.45cm 3 / g or 1.5cm 3 In other embodiments, the total pore volume is about 0.8 cm 3 / g to about 1.5cm 3 / g, about 0.8cm 3 / g to about 1.4cm 3 / g, about 0.8cm 3 / g to about 1.3cm 3 / g, about 0.8cm 3 / g to about 1.2cm 3 / g, or about 0.8cm 3 / g to about 1.1cm 3 / g.

[0315] In some embodiments, the pore size of activated carbon (or silane functionalized activated carbon) is greater than 1.45nm. In other embodiments, the pore size is greater than 1.5nm, 1.6nm, 1.7nm, 1.8nm, 1.9nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, or 9nm. In other embodiments, the pore size is about 1.45nm, 1.5nm, 1.6nm, 1.7nm, 1.8nm, 1.9nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, or 9nm. In some embodiments, the pore size of activated carbon (or silane functionalized activated carbon) is at least 1.5nm. In other embodiments, the pore size is at least 1.5nm, 1.6nm, 1.7nm, 1.8nm, 1.9nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, or 9nm. In other embodiments, the pore size is from about 1.5 nm to about 10 nm, from about 1.5 nm to about 9 nm, from about 1.5 nm to about 8 nm, from about 1.5 nm to about 7 nm, from about 1.5 nm to about 6 nm, or from about 1.5 nm to about 5 nm.

[0316] In some embodiments, the activated carbon (or silane-functionalized activated carbon) has a dye adsorption of at least 170 mg / g.

[0317] In other embodiments, the As(V) absorption capacity of the activated carbon (or silane-functionalized activated carbon) is at least 60 mg / g, 70 mg / g, 80 mg / g, 90 mg / g, 100 mg / g, 110 mg / g, or 120 mg / g. In other embodiments, the As(V) absorption capacity of the activated carbon (or silane-functionalized activated carbon) is about 60 mg / g, 70 mg / g, 80 mg / g, 90 mg / g, 100 mg / g, 110 mg / g, or 120 mg / g.

[0318] In other embodiments, the Se(VI) absorption capacity of the activated carbon (or silane-functionalized activated carbon) is at least 60 mg / g, 65 mg / g, 70 mg / g, 75 mg / g, 80 mg / g, 85 mg / g, 90 mg / g, or 95 mg / g. In other embodiments, the Se(VI) absorption capacity of the activated carbon (or silane-functionalized activated carbon) is greater than 60 mg / g, 65 mg / g, 70 mg / g, 75 mg / g, 80 mg / g, 85 mg / g, 90 mg / g, or 95 mg / g.

[0319] In other embodiments, the iodine value of the activated carbon (or silane functionalized activated carbon) is at least 500 mg / g, 550 mg / g, 600 mg / g, 650 mg / g, 700 mg / g, 750 mg / g, or 800 mg / g. In other embodiments, the iodine value of the activated carbon (or silane functionalized activated carbon) is greater than 500 mg / g, 550 mg / g, 600 mg / g, 650 mg / g, 700 mg / g, 750 mg / g, or 800 mg / g.

[0320] In other embodiments, the activated carbon (or silane-functionalized activated carbon) has a Rhodamine B adsorption capacity of at least 170 mg / g, 175 mg / g, 180 mg / g, 190 mg / g, 200 mg / g, 210 mg / g, or 220 mg / g. In other embodiments, the activated carbon (or silane-functionalized activated carbon) has a Rhodamine B adsorption capacity of greater than 170 mg / g, 175 mg / g, 180 mg / g, 190 mg / g, 200 mg / g, 210 mg / g, or 220 mg / g.

[0321] In other embodiments, the activated carbon (or silane-functionalized activated carbon) has a methylene blue adsorption capacity of at least 100 mg / g, 105 mg / g, 110 mg / g, 120 mg / g, 130 mg / g, or 140 mg / g. In other embodiments, the activated carbon (or silane-functionalized activated carbon) has a methylene blue adsorption capacity greater than 100 mg / g, 105 mg / g, 110 mg / g, 120 mg / g, 130 mg / g, or 140 mg / g.

[0322] In some embodiments, the activated carbon (or silane-functionalized activated carbon) has a cell viability greater than 90% after exposure for 24 hours at a concentration of 200 μg / mL. In other embodiments, the activated carbon (or silane-functionalized activated carbon) has a cell viability greater than 91%, 92%, 93%, 94%, or 95%. In this regard, the activated carbon is non-toxic to cells, organisms, and the environment.

[0323] In some embodiments, activated carbon (or silane-functionalized activated carbon) has a HepG2 cell viability greater than 90% after exposure to 24 hours and at a concentration of 200 μg / mL. In other embodiments, the HepG2 cell viability of activated carbon (or silane-functionalized activated carbon) is greater than 91%, 92%, 93%, 94% or 95%.

[0324] In some embodiments, the MRC5 cell viability of activated carbon (or silane-functionalized activated carbon) after exposure for 24 hours and at a concentration of 200 μg / mL is greater than 90%. In other embodiments, the MRC5 cell viability of activated carbon (or silane-functionalized activated carbon) is greater than 91%, 92%, 93%, 94% or 95%.

[0325] In some embodiments, the activated carbon (or silane-functionalized activated carbon) has a cell viability greater than 90% after 48 hours of exposure at a concentration of 200 μg / mL. In other embodiments, the activated carbon (or silane-functionalized activated carbon) has a viability greater than 91%, 92%, 93%, 94%, or 95%. In this regard, the activated carbon is non-toxic to cells, organisms, and the environment.

[0326] In some embodiments, the HepG2 cell viability of activated carbon (or silane-functionalized activated carbon) after exposure for 48 hours and at a concentration of 200 μg / mL is greater than 90%. In other embodiments, the HepG2 cell viability of activated carbon (or silane-functionalized activated carbon) is greater than 91%, 92%, 93%, 94% or 95%.

[0327] In some embodiments, the MRC5 cell viability of activated carbon (or silane-functionalized activated carbon) after exposure for 48 hours and at a concentration of 200 μg / mL is greater than 90%. In other embodiments, the MRC5 cell viability of activated carbon (or silane-functionalized activated carbon) is greater than 91%, 92%, 93%, 94% or 95%.

[0328] In some embodiments, activated carbon (or silane functionalized activated carbon) is synthesized from recycled pure carbon black (Carbon X). SEM and TEM analysis were performed to study the morphology of the activated carbon. The activated carbon was found to have a spherical shape with a particle size of 40-80 nm. In addition, the large surface area and increased pore volume of the activated carbon (AC-AP) were found to be 671 m 2 / g and 1.54cm 3 / g. It was found that the activated carbon had a high adsorption capacity for dyes present in aqueous solution due to its porous nature. This activated carbon can be used in other applications such as air purification, composite material reinforcement, and pigments in coatings. The results obtained indicate that the synthesized activated carbon can be considered as a low-cost, high-performance material for various industrial applications.

[0329] For example, AC-APs synthesized from carbon waste can be used for wastewater treatment, adsorption of harmful gases in the environment, reinforcement of composite materials, and pigments in inks.

[0330] Example

[0331] Material

[0332] Carbon X was obtained from Sembcorp Industries Ltd., Singapore. Ammonium persulfate was used as an activation catalyst, and ammonium hydroxide solution (28%), glacial acetic acid (99.7%), ethanol, ethylene glycol, rhodamine B, sodium arsenate heptahydrate, and sodium selenate were purchased from Sigma Aldrich. 1,2-Bis(triethoxysilyl)ethane used as a silane agent was purchased from Sigma Aldrich. All chemicals were used without further purification, and water used in all experiments was obtained from a Milli Q water system.

[0333] Characterization methods

[0334] The textural properties of carbon nanoparticles, such as surface area, pore volume and pore size, were measured using a Quantachrome Autosorb iQ C-XR. All samples were degassed at 200 °C for 6 h before N2 adsorption analysis. Fourier transform infrared spectroscopy was performed on a Bruker Vertex 70 spectrometer with a platinum attenuated total reflectance (ATR) module at 4000 and 400 cm -1 The functional groups of the carbon samples were analyzed by Raman spectroscopy between 1000 and 1800 cm-1 on a Bruker RAMII spectrometer. -1The carbon skeleton was recorded. The X-ray diffraction (XRD) pattern was characterized on a Bruker D8 Advance powder X-ray diffractometer. The morphology of the carbon material was examined by scanning electron microscopy (FESEM) (JEOL, JSM-7610F) at an accelerating voltage of 20 kV and by high-resolution transmission electron microscopy (FETEM) (JEM-2100F) at an accelerating voltage of 200 kV. The composition of the sample was studied using an elemental analyzer (EA, ThermoFisherScientific FlashSmart CHNS Elemental Analyser). The samples were analyzed on a Perkin Elmer SII (Diamond series) under a nitrogen atmosphere at 10 ° C min -1 The heating rate is from 30 to 900 °C for thermal stability of the material.

[0335] Adsorption studies

[0336] For adsorption studies, 10 mg of carbon sample was added to 20 ml of Rhodamine B (200 ppm), As (V) (200 ppm) and Se (VI) (200 ppm) solutions in 50 ml polypropylene tubes. The adsorption experiments were carried out in a mechanical shaker at 250 rpm for 6 h. After adsorption, the carbon particles separated by centrifugation and the dye solution concentration were analyzed by UV-Vis spectrophotometer. The concentrations of As (V) and Se (VI) were analyzed by ICP-OES. The iodine value and methylene blue value were obtained by using ASTM-D4607 and JISK 1474 methods, respectively.

[0337] Synthesis of Ammonium Persulfate Activated Carbon (AC-AP)

[0338] Briefly, a round-bottom flask containing 50 ml of water (pH 7-9 using ammonia) and 10 g of carbon X was vigorously stirred at room temperature for 1 h. Then, 2 g of ammonium persulfate (AP) was added to the mixture and further stirred for 1 h. The resulting mixture was heated at 400 ° C for 3-6 h to obtain porous activated carbon (AC-AP). An exemplary step-by-step synthesis process of activated carbon is described in Scheme 1.

[0339]

[0340] Scheme 1. Schematic diagram of activated carbon (AC–AP) synthesis

[0341] The method is also applicable to other carbon black materials, such as refinery carbon waste, converted into activated carbon.

[0342] Synthesis of Silane-functionalized Activated Carbon (AC-Si)

[0343] Silane-functionalized activated carbon was synthesized by functionalizing the surface of carbon X using bistriethoxysilane. Carbon X nanoparticles (10 g) were dispersed in a mixture of water (85 ml) and ethanol (15 ml). Carbon X was then fixed with silica by adding 2.6 ml of bistriethoxysilane and 1.2 ml of acetic acid to the above dispersion and ultrasonicated for 10 minutes. The mixture was stirred at room temperature for 3 h and then centrifuged to obtain silane-functionalized carbon X. The obtained silane-functionalized carbon X mixture was heated at 400 ° C for 3-6 h to obtain silane-functionalized activated carbon (carbon black-Si). An exemplary step-by-step synthesis of silane-functionalized activated carbon is described in Scheme 2.

[0344]

[0345] Scheme 2. Schematic diagram of the synthesis of silane-functionalized carbon (AC–Si)

[0346] Example 1

[0347] SEM images of carbon X, AC-AP, and AC-Si Figure 1 As shown in Figure 1 a and Figure 1 As shown in (b), the carbon X and CA-AP images show uniformly sized particles with spherical morphology. The particles are interconnected by weak forces and this interconnected network of particles is observed in all samples. It is observed that there are a large number of voids between the carbon particles due to the interconnected network structure. The morphology of AC-AP is not affected by the oxidation with ammonium persulfate. AC-Si shows dense dark particles (silicon dioxide) between the spherical carbon nanoparticles, which proves the functionalization of silane on carbon X, as shown in (c). Figure 1 As shown in c.

[0348] Example 2

[0349] The particle size and morphology of the carbon nanoparticles were examined using HR-TEM. The particle sizes of Carbon X and AC-AP were in the range of 40–80 nm, as shown in Figure 2. Figure 2 a and Figure 2 As shown in b. Figure 2 The interconnection of carbon nanoparticles is clearly observed in d. Figure 2 In c, the aggregation and stacking of carbon nanoparticles form a porous structure in an interconnected network. Figure 2 e shows the core-shell nanoparticle structure of AC-Si. Figure 2 The formation of a transparent silica shell on the carbon nanoparticles is clearly observed in f. The thickness of the silica shell is in the range of 10 nm and the core contains a minimum of 4-5 carbon nanoparticles. The functionalization of silane on carbon is consistent with the SEM results.

[0350] Example 3

[0351] Fourier transform infrared spectroscopy measurements were analyzed to identify the functional groups present in carbon X, AC-AP, and AP-Si, such as Figure 3 As shown in Figure 2, the spectra of all three carbon materials are different in the range of 1600–900 cm due to the chemical treatment and functionalization of the carbon. -1 Significantly different within the region. 1550 and 1760cm -1 The absorption peaks near 1760cm are attributed to CC and C=O stretching vibrations. -1 Compared with the (C=O) peak, 1550cm -1 A stronger peak appears at (CC), such as Figure 3 a. However, for AC-AP, compared with carbon X, 1760 cm -1 The peak at (C=O) is stronger because a greater number of functional groups are generated during the oxidation step, e.g. Figure 3 b. AC-Si shows all the peaks similar to those of AC-AP, as well as the peak at 1030 cm -1 The additional peaks of Si-O stretching vibration observed at , which proves the functionalization of silane groups on carbon nanoparticles, such as Figure 3 As shown in c.

[0352] Example 4

[0353] Raman spectroscopy was used to analyze the sp2 and sp3 carbon atoms present in the carbon nanoparticles. In all samples, the peaks at 1330 and 1590 cm-1, corresponding to the D and G bands, were -1 The peaks were observed at , indicating the graphite carbon skeleton, such as Figure 4 (ac) shown.

[0354] The D band represents the disordered structure of sp2 carbon atoms, and the G band represents the in-plane vibration of sp2 carbon. The D and G bands of all samples are broad, which indicates the amorphous nature of carbon nanoparticles, such as Figure 4 ac. The graphite structure of carbon X is not destroyed by the activation treatment, such as Figure 4 b and Figure 4 c. Graphite structure plays a vital role in enhancing textural properties such as increasing surface area and pore volume.

[0355] Example 5

[0356] The XRD patterns of carbon X, AC-AP and AC-Si are shown in Figure 5 The broad and strong peak at 25° (2θ) is a characteristic peak of the graphite structure, and the reflection observed at 43° (2θ) is due to the diamond (111) plane, as shown in Figure 5AC-AP and AC-Si still maintain a high graphite structure even after chemical and physical treatments. Figure 5 The peak at 25° (2θ) in b and 5c shows that AC-AP and AC-Si contain a high percentage of graphitic structure, which is consistent with the Raman results.

[0357] Example 6

[0358] The thermal stability of carbon nanoparticles was analyzed by TGA. The initial weight loss of carbon nanoparticles was due to the moisture content. Carbon X started to decompose at 520 °C and completely decomposed at around 850 °C, as shown in Figure 6 The decomposition of AC-AP starts at 480 °C. Due to the functional groups present in AC-AP, its stability is weaker than that of carbon X, as shown in Figure 6 b. After chemical and thermal treatment, functional groups (C=O, CO) are generated, which can reduce the thermal stability of carbon particles. AC-Si shows a similar trend relative to AC-AP. Figure 6 c shows that the residual mass fraction of Si in carbon black is high due to the presence of silica. The elemental analysis of the carbon sample was performed by CHNS analyzer, as shown in Table 1. After the activation process, the carbon percentage in the sample decreased. This is consistent with the TGA results.

[0359] Table 1. Elemental analysis of carbon nanoparticles.

[0360]

[0361] Example 7

[0362] The texture parameters of carbon nanoparticles were examined by surface area analyzer. Carbon X and AC-AP showed type II isotherms with H4 hysteresis loops, which indicated that the micropores ( Figure 7 (a and b)). AC-Si exhibits a type II isotherm with an H3 hysteresis loop, which indicates the presence of micropores and mesopores in the carbon structure ( Figure 7 c). The BET surface area (Multipoint BET), pore volume (BJH method) and pore size (BJH-method) of the carbon nanoparticles are listed in Table 2. The BET specific surface area of ​​AC-AP is higher than that of Carbon X due to the synergistic effect of ammonium persulfate and heating in the presence of air to form pores, which further increases the pore volume and pore size. Functionalization with a silane agent reduces the surface area due to the clogging of micropores. Crosslinking between carbon nanoparticles and silane agents can lead to mesopores, which increase the pore size of AC-Si. The pore size distribution of the carbon nanoparticles is shown in Figure 8Carbon X and AC-AP contain mainly micropores, while AC-Si contains both micropores and mesopores. The results of the N2 isotherm clearly show that the method developed in this study enhances the textural properties of carbon nanoparticles.

[0363] Table 2. Texture parameters of (a) Carbon X, (b) AC-AP, and (c) AC-Si

[0364]

[0365] Example 8

[0366] The adsorption capacities of As(VI), Se(VI) and iodine are as follows Fig. 9 As shown. Both As(V) and Se(VI) exist as anions at neutral pH. Both As(V) and Se(VI) have strong interactions with the functional groups present in AC-AP. AC-AP contains a large number of functional groups such as –COOH and –OH, which interact with heavy metal anions in solution. The negative charge of the anions (As(V) and Se(VI)) has a strong interaction with the positive charge of –C=O present in the carboxylic acid group in AC-AP. The –OH groups in AC-AP have an interaction with the hydrogen bonds between O=metal present in the metal anions to hold the metal ions in AC-AP. These interactions form chelation to capture the metal ions in AC-AP. Another important parameter is the microporous nature of AC-AP, where the functional groups present in the micropores are close to each other and can bind metal ions more effectively through strong chelation. In the mesopores, the adsorption capacity for a particular heavy metal decreases due to the increase in the distance between the functional groups. Carbon X has fewer functional groups and shows a lower adsorption capacity compared to AC-AP. AC-Si showed better performance for heavy metal and iodine adsorption compared to Carbon X, but lower than AC-AP. The large number of micropores resulted in high iodine value.

[0367] Example 9

[0368] The adsorption capacity of Rhodamine B and Methylene Blue is listed in Table 3. AC-AP shows high adsorption capacity for dyes compared to other carbon nanoparticles due to high surface area and pore volume generated during chemical and thermal treatment. After treatment, AC-AP produces a large number of micropores and mesopores. Due to the mesopores, the adsorption of dyes is increased compared to Carbon X. Mesopores play a major role in the adsorption of dyes since dyes are large molecules. AC-Si also shows better performance than Carbon X. Activated carbon from a commercial source (Continental Carbon) is shown in Table 3 as a control.

[0369] Table 3. Adsorption capacity of carbon nanoparticles

[0370]

[0371] Example 10

[0372] Figures 10a and 10b show that the viability of HepG2 and MRC-5 was affected by unleached carbon black waste in a dose- and time-dependent manner. Overall, cell viability decreased with increasing concentrations of unleached carbon black waste. At higher concentrations of 10 mg / mL, the viability of both cell lines was only below 10%. Within 24 hours, at low concentrations of unleached carbon black waste (0.25 mg / mL), the viability of HepG2 increased by more than 60%, but the viability of MRC-5 cells remained less than 10% at all concentrations tested. This result may indicate that MRC-5 is a cell model that is very sensitive to the toxicity of carbon black waste extracts. Considering this data, it is clearly proposed that fine and dusty carbon black waste can cause serious damage to human lungs when inhaled. After 48 hours of exposure, the dose dependence of survival became insignificant. After 48 hours of culture with unleached carbon black waste extracts at a concentration of ≥5 mg / mL, few cells survived. In general, for a given extract concentration, the viability after 48 h was lower than that after 24 h. Therefore, the results obtained from the MTS toxicity experiments suggest that longer exposure times lead to increased cytotoxicity.

[0373] Figure 10 shows the survival rate of human cell lines. (a) HepG2 cells cultured with unleached carbon black, (b) MRC-5 cells cultured with unleached carbon black, (c) HepG2 cells cultured with AC-AP, (d) MRC 5 cells cultured with AC-AP, (e) HepG2 cells cultured with AC-Si, (f) MRC 5 cells cultured with AC-Si samples at different concentrations for 24h and 48h exposure culture. Data represent the mean ± SD of three replicates per run.

[0374] Considering environmental safety, the obtained carbon black waste extract was leached and activated with ammonium persulfate (AC-AP) and silane-functionalized carbon (AP-Si). The toxicity of AC-AP and AC-Si was tested in the liver cancer HepG2 cell line and the normal lung MRC-5 cell line. Figures 10c, 10d, 10e and 10f show that within the wide concentration range tested, AC-AP and AC-Si have less toxic effects on HEPG2 and MRC-5 cells after 24 and 48 hours of culture. Therefore, the results indicate that AC-AP and AC-Si are safer and biocompatible for various environmental applications.

[0375] It will be understood that many further modifications and combinations of various aspects of the described embodiments are possible. Accordingly, the described aspects are intended to embrace all such changes, modifications and variations that fall within the spirit and scope of the appended claims.

[0376] In this specification and the appended claims, unless the context requires otherwise, the word "comprise" and variations such as "comprises" and "comprising", will be understood to imply the inclusion of a stated integer or step, or group of integers or steps, but not the exclusion of any other integer or step, or group of integers or steps.

[0377] Reference in this specification to any previous publication (or information obtained therefrom) or any known matter is not and should not be taken as an acknowledgement or approval or any form of suggestion that the previous publication (or information obtained therefrom) or known matter forms part of the common general knowledge in the field of endeavor to which this specification relates.

Claims

1. A method for forming silane-functionalized activated carbon, comprising: a) mixing carbon black with a silane agent and an activated catalyst in a polar solvent to form a mixture; and b) heating the mixture at 350° C. to 500° C. to form the silane-functionalized activated carbon; wherein the weight ratio of carbon black to activated catalyst is from 1:0.1 to 1:0.5; and wherein the activating catalyst is selected from acetic acid and / or ammonia, The silane agent is selected from bistriethoxysilane (1,2-bis(triethoxysilyl)ethane), 1,2-bis(trichlorosilyl)ethane, 1,2-bis(trimethoxysilyl)ethane or a combination thereof.

2. The method of claim 1, wherein the mixture is stirred at room temperature for at least 3 h.

3. The process according to claim 1 or 2, wherein the mixture is heated at 350°C for at least 6 h.

4. The method according to claim 1 or 2, wherein the weight ratio of carbon black to silane agent is 1:0.18 to 1:0.

25.

5. The method according to claim 1 or 2, wherein the weight ratio of the silane agent to the catalyst is 1:0.5 to 1:1.

7.

6. A silane-functionalized activated carbon formed by the method according to any one of claims 1 to 5.

7. The silane-functionalized activated carbon according to claim 6, having a particle size of 140 nm to 500 nm.

8. The silane-functionalized activated carbon according to claim 6 or 7, comprising at least 4 carbon particles.

9. The silane-functionalized activated carbon according to claim 6 or 7, which has a silica shell with a thickness of 10 nm on at least the surface of the activated carbon.

10. The silane-functionalized activated carbon according to claim 6 or 7, having a BET surface area greater than 600 m 2 / g.

Citation Information

Patent Citations

  • Preparation method for super activated carbon and method for recycling produced waste liquid and by-producing carbonate

    CN108117074A